Galectins and their involvement in ocular disease and development. (August 2020) - Luis, Joshua; Eastlake, Karen; Khaw, Peng.T.; Limb, G. Astrid
Abstract: Galectins are carbohydrate binding proteins with high affinity to ß-galactoside containing glycoconjugates. Understanding of the functions of galectins has grown steadily over the past decade, as a result of substantial advancements in the field of glycobiology. Galectins have been shown to be versatile molecules that participate in a range of important biological systems, including inflammation, neovascularisation and fibrosis. These processes are of particular importance in ocular tissues, where a major theme of recent research has been to divert diseases away from pathways which result in loss of function into pathways of repair and regeneration. This review summarises our current understanding of galectins in the context important ocular diseases, followed by an update on current clinical studies and future directions. Highlights: Galectins perform a wide range of intracellular and extracellular functions. Galectins-1, -3, -7, -8 and -9 are of particular relevance to ocular tissues. Within ocular tissues, galectins contribute to neovascularisation, inflammation and fibrosis. Current clinical trials are underway to explore the potential therapeutic effects of galectin inhibition.